Changes in Ovarian Functions Following Platelet-Rich Plasma (PRP) Injection and Its Impact on in Vitro Fertilisation (IVF) Treatment: A Pre-Post Research - Serap Simavlı; Emel Kiyak Caglayan; Ikbal Kaygusuz; Fatih Albayrak; Eray Caliskan (Clinical and Experimental Obstetrics & Gynecology)
Background: Giving birth is one of the challenges that women of reproductive age encounter when their ovarian reserve has decreased or been lost. Platelet-rich plasma (PRP) may be advantageous for women experiencing a poor ovarian response (POR). To evaluate the efficacy of administering autologous PRP injections into the ovary in improving ovarian reserve, oocyte and embryo production, and live birth rates in patients with a poor prognosis. Methods: The trial comprised 234 women in their reproductive years who had a diagnosis of POR and the Bologna criteria. These women received intraovarian PRP injections. The age range of the cases was between 30 and 44 years. Each ovary received a multifocal intramedullary injection of 3–4 mL of PRP. The effectiveness of PRP was evaluated in all patients, with a six-month follow-up to assess follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), and anti-Mullerian hormone (AMH). An evaluation was conducted on the metrics of in vitro fertilization (IVF) results and indications of ovarian reserve. Results: Subsequent to PRP treatment, there was a rise in both the quantity of antral follicles count (AFC) and the concentration of AMH in the bloodstream. After receiving PRP injection, 21 women (9.0%) became pregnant without any intervention, 9 women (3.8%) were excluded in the study anymore, 192 women (82.0%) attempted IVF treatment with developing antral follicles, 4 of whom have premature ovulation and 12 women (5.1%) who did not have antral follicles did not need any more therapy. Out of the 188 women who had IVF, 126 (67.0%) successfully developed embryos and 106 of them had the embryos transferred. Among these, 42 (39.6% per transfer) achieved pregnancy, and 39 (36.8% per transfer) had a continuing pregnancy resulting in a live birth. Conclusion: Autologous PRP injection into the ovary may be investigated as another experimental therapeutic option for women with POR.